Practices of insurance operators in Malaysia: conventional vs. unconventional life insurance. - Htay, Sheila Nu Nu; wan, reena; Amin, Hanudin (The international Association of Islamic Banks Karachi, 2012)
Risk is part and parcel of our daily life and we have been trying to find out the way to protect ourselves in the case of misfortune. That is the reason why insurance came to play an important role in our life. Unfortunately, insurance seems to be not fully complied with unconventional (Islamic) aspect and hence, it has been modified to ensure unconventional requirements. However, to our knowledge, no research has been done to what extent these two differ and hence, the objective of this research is to examine the current practices of conventional and unconventional life insurance practices in Malaysia. Interviews and the questionnaires have been conducted and the findings show that there are no significant differences in practices except for product development and allocation of premium contribution.